Carotid Body Tumor - A Case Reports - Hoque, Rezwanul; Hussain, Sabrina Sharmeen; Chowdhury, Md Abdul Quaium; Alauddin, Md; Sarker, Swadesh Ranjan; Alauddin, Md; Hossain, Md Aslam; Rahman, Md Mostafizur (University Heart Journal, 2012)
Carotid body tumor, an extra-adrenal paraganglioma, represents an uncommon entity arising in chemoreceptor tissue located at the carotid bifurcation. They commonly present as asymptomatic neck masses and careful preoperative evaluation is required to find out the functional and vascular status of these tumours. An unusual case of a large (70 × 50 × 45 mm) carotid body tumor of Shamblin type III in a 50 year old male is being presented here. The evaluation, management and the final outcome of this case of carotid body tumour is being reported here. DOI: http://dx.doi.org/10.3329/uhj.v8i1.11670 University Heart Journal Vol. 8, No. 1, January 2012